2005
DOI: 10.1097/00005650-200502000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the SARS Outbreak on an Urban Emergency Department in Taiwan

Abstract: The SARS catastrophe affected the ED visit volume, finances, various patient characteristics, and stress levels in the ED physicians and nurses. EDs must be fully prepared to face the challenges of the next outbreak of SARS or other infectious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 9 publications
5
81
0
3
Order By: Relevance
“…In the early outbreak period, pediatric visits decreased by 47%, similar to the 45% decline seen at one hospital in Taiwan 5 and the 48% reduction seen at a pediatric hospital in Toronto 6 when both were affected by SARS. In 2004, 1 year after SARS, ED visits returned to >90% of the pre-SARS levels for all age groups except infant/toddlers, which remained at 46% of the pre-SARS level (Table 1).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In the early outbreak period, pediatric visits decreased by 47%, similar to the 45% decline seen at one hospital in Taiwan 5 and the 48% reduction seen at a pediatric hospital in Toronto 6 when both were affected by SARS. In 2004, 1 year after SARS, ED visits returned to >90% of the pre-SARS levels for all age groups except infant/toddlers, which remained at 46% of the pre-SARS level (Table 1).…”
Section: Discussionmentioning
confidence: 58%
“…Similar SARS-related declines were reported in Hong Kong, where ED visits fell 24% and 51% in the two 2-week study periods, 3 and in Taiwan, where they fell by 33% at one hospital and 40% at another. 4,5 In contrast, during the 1993 E. coli 0157:H7 outbreak in the Washington state area, ED visits increased by 17% at one pediatric hospital over a 4-month period, the majority of which were assessments for other gastroenteritis illnesses. 2 Similarly, visits initially doubled during the Hantavirus outbreak in 1993, although this may have been related to a media campaign urging people to seek medical attention if they had flu-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the outbreak of SARS, there was also a social phenomenon of people avoiding not only hospital healthcare workers but also their families in fear of infection. [7][8][9][10]20 In Korea, it was reported that the children of nurses and doctors working at a hospital with MERS-CoV patients were not allowed to attend their kindergartens and schools, and the government initiated strong measures, including judicial punishment, against such a practice. 21 According to Koh et al, 9 there was a significant relationship between healthcare workers' stress during the outbreak of SARS and their cognitions of social stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Additionally, during the SARS catastrophes in Taiwan, Toronto, and Singapore, many nurses and doctors in EDs experienced psychological discomfort due to situations where they cared for patients with highly contagious diseases. [7][8][9] These previous cases, in which healthcare workers were exposed to the risk of fatal infection from a pandemic disease such as SARS, raised a pressing issue regarding healthcare workers' ethical problems in caring for patients who place them at risk of newly emerging infectious diseases. 10,11 According to the study by Maunder et al, 8 prominent psychological problems experienced by healthcare workers during the outbreak of SARS were fear, anxiety, anger, and frustration.…”
Section: Introductionmentioning
confidence: 99%